VD_FINDINFO Jug-inc / 2012 / 1 vom 29. November 2011 - VD Tribunal cantonal (2011)
SUSPENSION DE LA PROCÉDURE, EXÉCUTEUR TESTAMENTAIRE, LEGS, QUALITÉ DE PARTIE | 517 CC, 518 CC, 123 CPC, 123a CPC, 63 CPC